2010
DOI: 10.1177/1403494810379291
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Systemic conditions associated with areca nut usage: A literature review

Abstract: AN chewing adversely affects systemic health by damaging the vital organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 63 publications
0
45
0
Order By: Relevance
“…5 The deleterious effects of chewing tobacco and related products on oral and systemic health have been reported. 2,[6][7][8][9] Clinical studies 2,6-9 have reported the occurrence and progression of oral mucosal disorders such as oral submucous fibrosis and oral cancer, which have significantly higher levels of incidence in BQ chewers as compared with their respective controls (ie, those who do not use BQ). It has been reported that BQ chewing, either with or without tobacco, is an independent risk factor for oral cancer.…”
mentioning
confidence: 98%
“…5 The deleterious effects of chewing tobacco and related products on oral and systemic health have been reported. 2,[6][7][8][9] Clinical studies 2,6-9 have reported the occurrence and progression of oral mucosal disorders such as oral submucous fibrosis and oral cancer, which have significantly higher levels of incidence in BQ chewers as compared with their respective controls (ie, those who do not use BQ). It has been reported that BQ chewing, either with or without tobacco, is an independent risk factor for oral cancer.…”
mentioning
confidence: 98%
“…1,[3][4][5] Areca nut, an essential component of gutka, has been associated with several disorders, including epilepsy, hepatocellular carcinoma, metabolic syndrome, impaired glucose tolerance (IGT), and diabetes. 6 Slaked lime, areca nut, and powdered tobacco (the major constituents of gutka) are independent risk factors of periodontal inflammation and have also been shown to suppress the growth of cultured gingival keratinocytes and periodontal fibroblasts. 7,8 Studies 9, 10 have also reported that arecoline has a diabetogenic effect and may result in insulin resistance by obstructing insulin signaling.…”
mentioning
confidence: 99%
“…Therefore, a variety of symptoms such as facial flushing, dizziness, nausea with gastric upset, palpitation, and sweating were experienced in the betel nut chewers in our study. Notably, arecoline has been shown to devastate the oral tissues by diffusing through the oral mucosal tissues, resulting in leukoplakia, submucous fibrosis, and verrucous lesion, which are precancerous lesions with an incidence of 1-18% progression to oral cancer (Reibel, 2003;Javed et al, 2010). During the past two decades, betel nut chewing has become a serious public health problem in Taiwan.…”
Section: Discussionmentioning
confidence: 99%